Acute ethanol-induced liver injury is prevented by betaine administration - Arumugam, Madan Kumar; Chava, Srinivas; Perumal, Sathish Kumar; Paal, Matthew C.; Rasineni, Karuna; Ganesan, Murali; Donohue, Terrence M.; Osna, Natalia A.; Kharbanda, Kusum K. (Frontiers in Physiology, 2022)
Binge drinking is the most common form of excessive alcohol use. Repeated episodes of binge drinking cause multiple organ injuries, including liver damage. We previously demonstrated that chronic ethanol administration causes a decline in the intrahepatic ratio of S-adenosylmethionine (SAM) to S-adenosylhomocysteine (SAH). This decline causes impairments in essential methylation reactions that result in alcohol-induced fatty liver (steatosis) and other features of alcohol-associated liver disease (ALD). Co-treatment with betaine during chronic ethanol feeding, normalizes hepatocellular SAM:SAH ratio and alleviates many features of liver damage including steatosis. Here, we sought to examine whether betaine treatment similarly protects against liver injury in an alcohol binge-drinking model. We hypothesized that ethanol binge with prior or simultaneous betaine administration would prevent or attenuate acute alcohol-induced liver damage. Male C57Bl/6 mice were gavaged twice, 12h apart, with either 6g ethanol /kg BW or with an equal volume/kg BW of 0.9% NaCl. Two separate groups of mice (n=5/group) were gavaged with 4g betaine/kg BW, either 2h before or simultaneously with the ethanol or saline gavages. All mice were sacrificed 8h after the last gavage and serum and liver parameters were quantified. Ethanol binges caused a 50% decrease in hepatic SAM:SAH ratio and a >3-fold rise in liver triglycerides (p ≤ 0.05). These latter changes were accompanied by elevated serum AST and ALT activities and blood alcohol concentrations (BAC) that were ~three-times higher than the legal limit of intoxication in humans. Mice that were treated with betaine 2h before or simultaneously with the ethanol binges exhibited similar BAC as in mice given ethanol-alone. Both betaine treatments significantly elevated hepatic SAM levels thereby normalizing the SAM:SAH ratio and attenuating hepatic steatosis and other injury parameters, compared with mice given ethanol alone. Simultaneous betaine co-administration with ethanol was more effective in preventing or attenuating liver injury than betaine given before ethanol gavage. Our findings confirm the potential therapeutic value of betaine administration in preventing liver injury after binge drinking in an animal model.